Disciplining Statistics : Demography and Vital Statistics in France and England, 1830-1885 - Schweber, Libby (Book collections on Project MUSE., 2006)
Disciplining Statistics contrasts the different ways that statistical knowledge was developed and used in England and France during the nineteenth century.